A patient caregiver survey in Indonesia: Knowledge and perception of antibiotic use and microbial resistance - Fauna Herawati; Setiasih; Muznah M. Alhabsyi; Willyam Gunawan; Debora E. Palijama; Lusiana F. Diah; Nabila A. Adriansyah; Rika Yulia; Christina Avanti (Elsevier, 2020)
Background: A successful antibiotic stewardship program depends not only the knowledge and perceptions of healthcare providers but also patients and caregivers. Accordingly, the caregiver will decide to give the medication for their children. This survey was conducted to observe the caregivers' knowledge and perceptions of antibiotic use and antibiotic resistance; and their relationship. Methods: We developed 14 item questions in a knowledge questionnaire and 30 item questions in a perception questionnaire. The knowledge questionnaire was measured by a Guttman scale, with 'Yes' or 'No' answers, while the perception questionnaire used a five-point Likert scale. Results: The knowledge about antibiotic resistance is low, while the knowledge about antibiotic administration was the highest score. Caregivers' perceptions and beliefs about antibiotic use and antibiotic resistance were mostly in the neutral category. The association between knowledge and perceptions about antibiotic use and antibiotic resistance in this study was weak. Conclusions: The caregivers' knowledge about antibiotic use was identified to be sufficient, particularly, the antibiotic definition (highest score). The caregivers' belief about antibiotic use and microbial resistance was neutral (3.5-3.7).